Implementasi Model Pembelajaran Think, Pair, Share Berbantu Video Kasus untuk Meningkatkan Kompetensi Literasi Numerasi Siswa Kelas VII SMP Muhammadiyah 4 Pambon pada Materi Ekosistem: (Implementation of the Think, Pair, Share Learning Model Assisted by Case Videos to Improve Numeracy Literacy Competence of Grade VII Students of Muhammadiyah 4 Pambon Middle School on Ecosystem Material) - Rahmawati, Susi; Percatawati, Dhea; Valentina, Ratna; Retnani, Dwi Ari Budhi; Herawati, Elysabet; Rosida, Aprilia (BIODIK, 2025)
This research aims to find out more about efforts to increase numeracy literacy skill of class VII students of SMP Muhammadiyah 4 Prambon by utilizing the Think, Pair, Share learning model with the support of case videos. This research is Classroom Action Research (CAR) conducted collaboratively with class teachers in 2 cycles. The subjects in this research were 13 grade VII students of SMP Muhammadiyah 4 Prambon. Methods of gathering data include observation, interviews, assessments, field notes, and documentation. The assessment consists of questions tailored to the benchmarks of numeracy literacy skills. The question format is a descriptive. The study’s findings indicated that there was a rise in numerical literacy prooficiency in every measure. The firs indicator in cycle 1 had an average value of 63, then in cycle 2 it became 81. The second indicator in cycle 1 had an average value of 62, then in cycle 2 it increased to 78. The third indicator in cycle 1 had an average value of 63, then in cycle 2 the average value was 80. Based on the results of the study, it can be concluded that the application of Think, Pair, Share learning model with the support of case videos can improve students numeracy literacy skill. Key words: Think, Pair, Share learning model, Numeracy literacy skill